Phytoalexins produced in the leaves of Capsella bursa-pastoris (shepherd’s purse) - Jimenez, L.D.; Ayer, W.A.; Tewari, J.P. (Phytoprotection, 1997)
Three phytoalexins, camalexin (C11H8N2S), 6-methoxycamalexin (C12H10N2SO), and N-methylcamalexin (C12H10N2S), were isolated from shepherd's purse (Capsella bursa-pastoris) challenged by Alternaria brassicae. N-methylcamalexin has not been reported previously. Phytoalexin elicitation in shepherd's purse is associated with its resistance to A. brassicae, a pathogen which causes an important disease of cruciferous crops in many parts of the world.